(untitled) (Research, Society and Development, 2024)
The main objective of this research is to identify the learning strategies that are applied to promote the development of oral production skills in the English language to secondary education students. This study uses mixed methodology that involves combining both approaches, both quantitative and qualitative, it is designed in non-experimental analytical studies. For the sample, the total number of language teachers (4) and 108 students selected through simple random sampling were taken. Two surveys were used to collect data, consisting of ten and 13 questions. The Excel and SSPS programs were used to analyze the data and prepare the frequency tables. It concluded that there is little use of teaching resources and strategies that enhance the learning and development of oral production in students. However, regarding the perception that students have about whether they understand when the teacher speaks to them in English, according to the findings found through the surveys, it is observed that 47.2% almost always understand, which represents relevant data. , and it can be said that teachers are making efforts to meet the objective, so that students learn enough through oral comprehension, but this effort must be accompanied by the ideal strategies to achieve the desired result.